Design, Synthesis and Molecular Docking Studies of Some Novel Spiro Derivatives By 1,3-Cycloaddition Reaction - Hasmaruddin, Nurul Syazana; Osman , Hasnah; Mohamed Yusoff, Nadia; Ali, Mohamed Ashraf Ali; Hassan, Mohd. Zaheen (2016)
Synthesis of polycyclic compounds having spiro nucleus has attracted the attention of synthetic organic chemists because of their highly pronounced biological activities such as antiviral, antimicrobial etc. Therefore, the development of new, rapid, and clean synthetic routes of such compounds is of great importance to both medicinal and synthetic chemists. The 1,3-dipolarcycloaddition reactions are proved to be an efficient method for regio and stereo selective synthesis of structurally complex spiro heterocycles from relatively simple precursors. Molecular docking provides a consistent and more precise picture of the interaction of biologically active molecules at the receptor level thereby facilitating the designing of novel therapeutic agents. Therefore, potency of the spiro compounds (4i) was evaluated preliminary through the molecular docking studies. Later substitutions were made in the reference molecule to get the potent compounds.